DNA repair and apoptosis: Roles in radiotherapy-related acute reactions in breast cancer patients - Batar, Bahadir; Mutlu, Tuba; Bostanci, Merve; Akin, Mustafa; Tuncdemir, Matem; Bese, Nuran; Guven, Mehmet (Cellular and Molecular Biology, 2018)
Normal tissue reactions are therapy limiting factor for the effectiveness of the radiotherapy in cancer patients. DNA repair and apoptosis are estimated to be critical players of adverse effects in response to radiotherapy. Our aim was to define the association of DNA repair (ERCC1 and XPC) and apoptotic (BCL2, CASP3 and NFKB1) gene expression, DNA damage levels, apoptosis changes and DNA repair gene variations with the risk of acute side effects in breast cancer patients. The study included 100 women with newly diagnosed breast cancer; an experimental case group (n=50) with acute side effects and the control group (n=50) without side effects. Gene expression was analyzed by reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR). Micronucleus (MN) and 8-hydroxy-2"²-deoxyguanosine (8-OHdG) assays were performed to compare the DNA damage levels. Apoptosis was examined by TDT-mediated dUTP-biotin nick end-labeling (TUNEL) staining. ERCC1 rs3212986 and XPC rs3731055 polymorphisms were genotyped by real-time PCR technique. No significantly correlation of DNA repair and apoptosis gene expression and DNA damage levels with acute side effects in response to radiotherapy. Also, there was no association between apoptosis levels and acute effects. ERCC1 rs3212986 CC genotype showed a protective effect against radiotherapy-induced acute reactions (p<0.001; OR: 0.21; 95% CI= 0.08-0.52). Our results suggest that apoptosis and DNA damage levels are not associated with acute radiosensitivity. DNA repair may affect the risk of acute reactions. Further studies are needed to validate the current findings.